Probability of glacial lake outburst flooding in the Himalaya - Litan Mohanty (Resources, Environment and Sustainability, 2021)
The present study aims to determine the probability of glacial lake outburst flooding (GLOF) in the Himalaya. Here, a total of 4198 glacial lakes with larger dimensions (>0.01 km2) were considered. A fusion between Object-based classification (OBC) and Analytical Hierarchy Process (AHP) was applied for unbiased results, involving the fifteen most essential predictors. The previously studied threshold values of predictors were used in OBC to determine GLOF prone lakes. On the other hand, earthquake, lake freeboard, moraine dam steepness, avalanches, and lake size change rate were prioritized for the AHP method. Individually, OBC and AHP methods identified 107 and 224 critical lakes. However, as a fusion of the above techniques (GIS overlay analysis), our study identified 60 critical lakes, followed by 164 and 3974 glacial lakes with medium and lower probability of GLOF. 95% of the higher GLOF-probable lakes are concentrated in the Kosi (33), Pelkhu (7), and Tista (5) river basins; sub-regionally coincide with Sikkim, Everest, Bhutan and Langtang region.